Classifying ASEAN Tourist Markets for Indonesia’s Tourism Strategy - Ramiz Ansharil Haq (ASEAN Journal on Hospitality and Tourism, 2026)
This study examines the expenditure behaviours of international tourists from ASEAN nations in Indonesia employing the Boston Consulting Group (BCG) Matrix to categorise countries according to market growth and relative market share. Data from the Indonesian Central Bureau of Statistics (2023–2024) indicates that Malaysia and Singapore are the primary providers to tourism earnings, but Brunei, Thailand, and the Philippines exhibit notable increase. The research classifies countries into four quadrants: Stars (Malaysia, Philippines, Myanmar, Vietnam and Thailand), Cash Cows (Singapore), and Question Marks (Brunei, Laos, Cambodia). Development plans are advised for each quadrant, including the enhancement of culture-based services, the expansion of flight routes, and regional collaboration. These findings offer guidance for stakeholders in formulating marketing strategies and resource distribution to optimise Indonesia's tourist potential.